METHODS OF CREDIT RISK MANAGEMENT IN COMMERCIAL BANKS AND THEIR IMPROVEMENT (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Credit risk management is a critical function in commercial banking, aimed at ensuring the stability and profitability of the financial institution. This paper explores various methods of credit risk management currently employed by commercial banks, including credit scoring, portfolio diversification, risk-based pricing, credit derivatives, and collateral management. Furthermore, it examines the limitations of these traditional methods and proposes enhancements to improve their effectiveness. The proposed improvements include the integration of advanced analytics and machine learning techniques for more accurate risk assessment, the adoption of automated monitoring systems for real-time tracking of credit exposures, the implementation of comprehensive stress testing frameworks, and the strengthening of regulatory compliance and internal controls. Additionally, the paper highlights the importance of ongoing staff training and the use of fintech innovations to enhance credit risk management practices. By adopting these improved methods, commercial banks can better manage their credit risk, leading to increased financial stability and performance.